THE ANALYSIS OF PSYCHOLOGHY OF INVESTORS IN MAKING INVESTMENT DECISIONS - M. Randy Pratama Jasmi (Jurnal Ilmiah Mahasiswa FEB, 2015)
This qualitative study aims to analyze the psychology of investor in making investment decision. Fundamental analysis and technical analysis are performed in this study. The method used to answer the research question is descriptive qualitative. Furthermore, the data collection method used in this study is in-depth interview. The results reveal that psychology has a role in the behavior of investors in making investment decisions and not only use fundamental analysis and technical analysis to analyze the stock prices. Furthermore the psychology of investors, such as: overconfidence, optimistic and pessimistic may influence the investment decisions. In addition the rational investor can reduce the chances for loss and can form an effective market in the stock market to the contrary irrational investors tend to get possibility of higher loss and can increase the volume of transactions on the stock market.Key words: Psychology Investment, Investment Decisions, Fundamental Analysis, Technical Analysis, Investor Psychology, Rational, Irrational.